2003
DOI: 10.1093/jn/133.3.689
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fats Differentially Modulate the Expression of Lecithin:Cholesterol Acyltransferase, Apoprotein-A1 and Scavenger Receptor B1 in Rats

Abstract: In the present study the effects of dietary fat with defined fatty acids on lecithin:cholesterol acyltransferase (LCAT) and apoA-1, the two components of HDL that play a major role in reverse cholesterol transport (RCT), were examined. In addition, the expression of scavenger receptor B1 (SR-B1), the receptor involved in the uptake of HDL core lipids, was also determined under the same conditions in rats fed semisynthetic diets supplemented with triolein (TO), tripalmitin (TP) or menhaden oil (MO). Serum LCAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 55 publications
1
16
0
2
Order By: Relevance
“…This particular observation is in line with that of Machado et al [5], who have reported less weight gain in mice fed a TFA diet than in those on a PUFA diet. Furthermore, in the present study, TFA- and n–3 PUFA-fed rats had significantly lower plasma TC and HDL-C levels while MUFA- and n–6 PUFA-fed rats had significantly higher plasma TC and HDL-C levels, which is in line with the observation of Hatahet et al [14]. However, the proportion of HDL-C in TC was not altered by any of these dietary treatments.…”
Section: Discussionsupporting
confidence: 92%
“…This particular observation is in line with that of Machado et al [5], who have reported less weight gain in mice fed a TFA diet than in those on a PUFA diet. Furthermore, in the present study, TFA- and n–3 PUFA-fed rats had significantly lower plasma TC and HDL-C levels while MUFA- and n–6 PUFA-fed rats had significantly higher plasma TC and HDL-C levels, which is in line with the observation of Hatahet et al [14]. However, the proportion of HDL-C in TC was not altered by any of these dietary treatments.…”
Section: Discussionsupporting
confidence: 92%
“…Feeding hamsters with miristic acid (a SAFA) modulates the SR-BI expression in the liver [34] . An increase in SR-BI expression was observed after feeding rats with oleic acid (a MUFA) [35] or in hamsters fed with omega-6 PUFAs [36] . Recently, an increase in hepatic mRNA levels for SR-BI was observed in mice fed omega-3 PUFAs [37] .…”
Section: Introductionmentioning
confidence: 99%
“…A metabolic effect similar to that reported in SR-BI-overexpressing mice [34] was observed in our study with rats fed the FO-diet ( fi g. 2, 4 a). Studies evaluating a possible regulatory link between dietary fatty acids and hepatic SR-BI expression have been previously reported [34][35][36][37] . Hamsters fed miristic acid [34] , a SAFA, showed a reduction of protein SR-BI expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Este efecto se ratifica en nuestro estudio, que muestra un significativo aumento del HDL-colesterol de un 97% en el grupo tratado. Ello se podría explicar porque, en respuesta a una dieta alta en grasas, se genera una probable disminución en la captación hepática de HDL por una regulación negativa del receptor de HDL (Scavenger Receptor B1 -SRB1), dificultando el transporte reverso de colesterol 33 . Adicionalmente, dietas bajas en grasas a largo plazo han mostrado un incremento en los niveles plasmáticos de triglicéridos 29 .…”
Section: Discussionunclassified